2006
DOI: 10.1007/s10745-006-9054-9
|View full text |Cite
|
Sign up to set email alerts
|

Why Folkbiology Matters: Resource Conflict Despite Shared Goals and Knowledge

Abstract: There is a continuing controversy over Native American fishing and hunting rights. We show that Native American (Menominee) and European American fish experts have a common knowledge base and share values and attitudes associated with fishing practices (though organized around different ethical principles). Nonetheless, perceived group differences are dramatic (especially European American perceptions of Native Americans). Cultural differences in models of nature and associated inference processes appear to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…This order effect, interesting in and of itself, is consistent with Medin and Waxman's (2007) analysis of the sources underlying asymmetries in inductive reasoning tasks. They proposed that the distinctive features of a target (including its distinctive category label) will reduce generalization from a base to a target.…”
Section: Methodological Issuessupporting
confidence: 83%
See 1 more Smart Citation
“…This order effect, interesting in and of itself, is consistent with Medin and Waxman's (2007) analysis of the sources underlying asymmetries in inductive reasoning tasks. They proposed that the distinctive features of a target (including its distinctive category label) will reduce generalization from a base to a target.…”
Section: Methodological Issuessupporting
confidence: 83%
“…We briefly describe our populations below (see Medin et al, 2006; Medin et al, 2007 and Ross et al, 2007 for additional background and details on the Wisconsin populations). In each of the three populations (urban, rural, Menominee), children were drawn from three age groups: 4- to 5-year-olds, 6- to 7-year-olds, and 9- to 10-year-olds.…”
Section: Methodsmentioning
confidence: 99%
“…Here, images serve as "discursive power" (Foucault 1980) and must therefore be analyzed as part of the power dynamics where stakeholders are defending or exerting their interests by positioning themselves relative to each other in the competition for resources. Therefore, images, including those stakeholders have of each other, have implications for negotiation and an ability to resolve conflicts, reach goal consensus, and secure compliance (Medin et al 2007). At the end of the day, images have a major impact on the governability of MPAs and hence their success.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that these differences in epistemological orientations foster greater attention to ecological relations in Native communities and a greater tendency to see humans as an integral part of ecosystems. In support of this idea, research by Medin et al (2006), Medin, Ross, Cox, and Atran (2007), and Ross, Medin, Coley, and Atran (2007) with European American and Menominee hunters and fishermen indicated that Menominees were more likely to organize their knowledge in terms of ecological relations and more likely to categorize on the basis of habitat than were European Americans. Related developmental work using an inductive inference task provides evidence that Menominee children are precocious with respect to engaging in ecological reasoning (Ross, Medin, Coley, & Atran, 2003).…”
Section: Epistemologies In Practicementioning
confidence: 95%